Marketing Efficiency Analysis Of Leafy Vegetable At Giant Extra Botanical Square, Bogor City - Khairi, Yudri; Yusdiarti, Arti; Miftah, Himmatul (Universitas Djuanda Bogor, 2017)
Leaf vegetables are in great demand by the people in Bogor City who are mostly from Sunda tribe. Bogor city residents who buy vegetables at Giant Extra Botani Square willing to pay more than those who buy in traditional markets. The research aimed to analyze marketing efficiency of leaf vegetables especially spinach, chinesse green cabbage (Brassica chinensis var. Parachinensis), kale, lettuce head and chinesse white cabbage (Brassica pekinensia L) at Giant Extra Botany Square in Bogor City . Data were analyzed descriptively and quantitatively with marketing margin, farmers share and R/C Ratio analysis. Primary data collection was taken from interview with Giant Extraâs management by purposive method, while interview to supplier and farmer used snowball sampling method. The results showed that the marketing efficiency of leaf vegetables in Giant Extra Botanical Square Bogor City, based on marketing margin analysis obtained the largest margin value on Chinese White Cabbage (Brassica pekinensia L) commodity amounting to Rp 20.450. Suppliers get the greatest benefits on commodities of spinach, Chinese Green Cabbage and kale. The highest farmers share was obtained by farmers in lettuce head commodities by 69.6%. The highest R/C ratio was obtained by Chinese White Cabbage commodity at 1.60Keywords: marketing efficiency, leavy vegetables, modern market